2021
DOI: 10.3389/fpubh.2021.744100
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Network and Reinforcement Learning Model for COVID-19 Prediction

Abstract: Detection and prediction of the novel Coronavirus present new challenges for the medical research community due to its widespread across the globe. Methods driven by Artificial Intelligence can help predict specific parameters, hazards, and outcomes of such a pandemic. Recently, deep learning-based approaches have proven a novel opportunity to determine various difficulties in prediction. In this work, two learning algorithms, namely deep learning and reinforcement learning, were developed to forecast COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…A DNN is a basic neural network with more hidden nodes. An intensive computation of the input is conducted in the neural network because of the nonlinear transformation from each hidden layer to the output layer [ 34 ]. However, DNN is more efficient than the superficial network.…”
Section: Methodsmentioning
confidence: 99%
“…A DNN is a basic neural network with more hidden nodes. An intensive computation of the input is conducted in the neural network because of the nonlinear transformation from each hidden layer to the output layer [ 34 ]. However, DNN is more efficient than the superficial network.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, although reinforcement learning has been applied, it has not typically been combined with 2D map analysis or lack external validation. 38 39 In this article, we demonstrate the use of a reinforcement-based DL GRU model with 2D choropleth maps to analyse spatial representation of results in order to rank the efficacy of various control measures. The proposed model is embedded in an interactive dashboard linked to the Government UK website and an expert-curated matrix to incorporate effects of control measures and social demographic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…From cardiovascular disease [131], to pandemic research [132], various methods had been considered and notable methods presented. Machine learning in particular showed an exponential increase in COVID-19 research where novel methods proposed [133][134][135][136][137][138][139][140]. It has been shown that ensemble, deep learning, and hybrid methods are rapidly getting popularity as also stated in previous surveys, for example, [140][141][142][143][144][145][146].…”
Section: Discussionmentioning
confidence: 99%